Economic integration across borders : the Polish interwar economy 1921-1937 - Carsten Trenkler; Nikolaus Wolf (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
In this paper we study the issue of economic integration across borders for the case of Poland's reunification after the First World War. Using a pooled regression approach and a threshold cointegration framework we find that the Polish interwar economy can be regarded as integrated with some restrictions. Moreover, a significant negative impact of the former partition borders on the level of integration that can be found for the early 1920s vanishes in the middle of the 1920s. This suggests that the integration policy after the reunification of Poland in 1919 was surprisingly successful.
Keywords: F15; N94; C22; N74; C32; E31; 330; Economic integration; Border effects; Law of one price; Poland; Threshold cointegration